Measuring the quality of pressure ulcer prevention: A systematic mapping review of quality indicators - Kottner, Jan; Hahnel, Elisabeth; Lichterfeld‐Kottner, Andrea; Blume‐Peytavi, Ulrike; Büscher, Andreas (International wound journal, 2018)
The aim of this study was to provide a systematic overview of available pressure ulcer prevention quality indicators and to evaluate the underlying empirical evidence. A systematic mapping review was conducted with combined searches in Embase and Medline, and websites of relevant institutions and organisations. The eligibility criteria were clear use of the term “quality indicator” regarding pressure ulcer prevention; English or German language; and all settings, populations, and types of resources, including articles, brochures, and online material. In total, n = 146 quality indicators were identified. Most indicators were published in the United States (n = 50). The majority of indicators was developed for the hospital setting (n = 102). Process indicators were the most common (n = 71), followed by outcome indicators (n = 49). Less than half of identified indicators appeared to be practically used. Evidence supporting the validity and reliability were reported for n = 25 and n = 30 indicators respectively. The high number of indicators demonstrate the importance of measuring pressure ulcer prevention quality. This is not an indicator of our ability to accurately measure and evaluate this construct. There is an urgent need to develop evidence‐based and internationally comparable indicators to help improve patient care and safety worldwide.